Implementasi Pembelajaran Diferensiasi pada Mata Pelajaran Sejarah: Studi Kasus di SMAN 23 Kabupaten Tangerang - Jumiarti, Dede Novita; Fakhruddin, M.; Marta, Nur Aeni (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This article describes the implementation of differentiated learning in history subjects at SMAN 23 Tangerang Regency. This research method uses qualitative methods, with a single case study strategy. The research method in this study is a qualitative method. The validity of the data used in this research uses triangulation of data sources and methods. The data was obtained through in-depth interviews, observation and document study. Research results: First, the history teacher's learning planning has prepared and implemented a history module that uses a differentiated learning approach. Second, implementation of learning, history teachers apply learning in the form of differentiation of content, processes and products for material on ancestral origins, four theories of ancestral origins, and their relationship to current Indonesian society. Third, learning evaluation, teachers use assessments based on cognitive, affective and psychomotor aspects. Fourth, the impact of differentiated learning in history subjects is improving critical and creative thinking skills in history learning. Fifth, the obstacles experienced are inadequate facilities and infrastructure, and also insufficient learning time.